Philippines : Report for the July 2004 Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2004)
This paper focuses on 2004 Post Program Monitoring Discussions for the Philippines. The authorities are formulating a significant package of tax measures. IMF staff argued that the bulk of the additional revenues should be saved, thereby front-loading the medium-term deficit reduction effort. Such a strategy would boost market confidence and exploit the likely greater potential to enact tax measures at the beginning of the new administration's term. The authorities are now also considering the power sector reforms.